1997
DOI: 10.3168/jds.s0022-0302(97)76143-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diet and Bovine Somatotropin on Heifer Growth and Mammary Development

Abstract: Forty Holstein heifers [body weight (BW) = 126 kg] were blocked by BW into groups of 4, and, within each block, heifers were randomly assigned to one of four treatments. Twenty heifers had ad libitum access to a diet formulated to produce a BW gain of 0.8 kg/d (control diet), and 20 heifers had ad libitum access to a diet formulated to produce a BW gain of 1.2 kg/d. (high diet). Half of the heifers fed each diet were injected daily with bovine somatotropin (bST; 25 micrograms/ kg of BW). The high diet increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
65
8
22

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(107 citation statements)
references
References 28 publications
12
65
8
22
Order By: Relevance
“…Heifers on treatment 2 attained puberty 15.1 d earlier than did control heifers with no significant difference in WH (Table 4). Similar results were obtained by Radcliff et al (1997), as high-CP, high-energy diet increased BWG and decreased age at puberty but had no effect on WH at puberty. The implantation of Synovex-C to heifers on treatment 3 induced earlier puberty by 38.1 d as compared with the control heifers (P<0.08), and their WH was shorter by 4.5 cm (P<0.08).…”
Section: Feed Intake and Efficiencysupporting
confidence: 82%
See 1 more Smart Citation
“…Heifers on treatment 2 attained puberty 15.1 d earlier than did control heifers with no significant difference in WH (Table 4). Similar results were obtained by Radcliff et al (1997), as high-CP, high-energy diet increased BWG and decreased age at puberty but had no effect on WH at puberty. The implantation of Synovex-C to heifers on treatment 3 induced earlier puberty by 38.1 d as compared with the control heifers (P<0.08), and their WH was shorter by 4.5 cm (P<0.08).…”
Section: Feed Intake and Efficiencysupporting
confidence: 82%
“…Although BW and wither height (WH) are closely correlated (Heinrichs and Hargrove, 1987;Heinrichs et al, 1992), the correlation between WH and primiparous milk production was higher than that observed between yield and BW (Heinrichs and Hargrove, 1987;Heinrichs et al, 1992;Markusfeld and Ezra, 1993). Compensatory growth of heifers was found to be limited (Ryan, 1990;Barash et al, 1994 a,b;Radcliff, 1997). Implantation of Synovex-C in 3-months-old beef heifers significantly enlarged their pelvic area before calving and tended to reduce calving difficulties (Deutscher et al, 1991;Rusk et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Desta forma, o crescimento dos animais pode ter sido limitado pela proteína da dieta, sendo o excesso de energia convertido em gordura. Radcliff et al (1997) afirmaram que o elevado ganho de peso para novilhas deve ser acompanhado de crescimento para evitar que fiquem excessivamente gordas, com maior possibilidade de terem partos distócicos.…”
Section: Resultsunclassified
“…Results from Capuco et al (1995), Radcliff et al (1997 and and Waldo et al (1998) indicated that mammary development could be either reduced or increased when feeding in excess or injecting bovine somatotropin before puberty. In both studies, no effect was noted on subsequent milk yield.…”
Section: Nutritional Factorsmentioning
confidence: 99%